2003
DOI: 10.1167/iovs.02-0863
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion with the Olfactomedin Domain of Myocilin Does Not Affect Outflow Facility

Abstract: Although the olfactomedin domain appears to be important for the function of myocilin, perfusion with a recombinant myocilin fragment containing this domain does not change outflow facility. It is possible that both the olfactomedin and N-terminal domains (including the leucine zipper) must be present for myocilin to have full function. Alternatively, posttranslational modifications of myocilin may have a major impact on protein function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 19 publications
1
34
0
Order By: Relevance
“…Therefore, it will be important to identify factors influencing this processing. In accordance with our results and as mentioned above, Goldwich et al (55) found that long term myocilin production in 293 EBNA cells resulted in significant increase of N-and C-terminal fragments of the protein.…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, it will be important to identify factors influencing this processing. In accordance with our results and as mentioned above, Goldwich et al (55) found that long term myocilin production in 293 EBNA cells resulted in significant increase of N-and C-terminal fragments of the protein.…”
Section: Discussionsupporting
confidence: 94%
“…Four findings sustain that the 35-kDa myocilin fragment is not a product of nonspecific degradation: (i) general proteinase inhibitors do not affect its production, as Goldwich et al also observed (40); (ii) deletion of the cleavage site inhibits the production of the 35-kDa fragment; (iii) the 35-kDa fragment originates intracellularly, probably in the ER and; (iv) different pathogenic mutations also inhibit the endoproteolytic cleavage. Interestingly, one such reported fragment was produced by 293 EBNA cells as a doublet, and it was determined that it matched the C-terminal region of myocilin, starting at the amino acid residue Leu 215 (40), in a place close to the cleavage site reported here. These data raise the possibility that proteolysis might occur at other nearby sites.…”
Section: Discussionmentioning
confidence: 57%
“…Several studies have reported the existence of myocilin fragments of ϳ30 -35 kDa in samples of recombinant myocilin expressed in cell lines and in tissue extracts (36,40,42). These fragments were usually interpreted as products of nonspecific myocilin proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…1A). Published data suggest that the C-terminal fragment of myocilin is secreted (3,23,66), while data concerning secretion of the N-terminal fragment are controversial (23,66). To test whether N-and C-terminal fragments of myocilin are (52) and anti-FLAG antibodies, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%